A longitudinal study on the imaginary of future physics teachers about 'learning assessment' - Nardi, R. [UNESP]; Belissimo, J. R. [UNESP]; Parma, F. W. [UNESP] (IOP Publishing, 2019)
We present here partial results of a broader study aimed to investigate details of the initial education of Physics teachers, seeking to analyse the representations of these future high school teachers, from admission until their graduation from university, in order to understand how research has been introduced in or affected their early training. In this sense, we sought to analyse the profile of these future teachers and their imaginaries about scientific knowledge, science teaching and the constitution of teaching knowledge, from the moment of joining university in 2014 until the completion of the programme in 2017. Data collection took place in accord with a qualitative approach, using questionnaires applied at the beginning of each academic year in the specific courses of the programme. The data were treated by Discourse Analysis, originated by Pecheux and developed in Brazil by Orlandi and other researchers. In this paper, we highlight the meanings produced in the discourses of future teachers on the theme learning assessment. The discourses show that the conditions of discourse production were fundamental in the changes of the future teachers' imaginaries about this theme, and the power and impact that the programme and the institution have on the future teachers.